Characterization and Expression Profiling Analysis of Calmodulin Genes in Response to Salt and Osmotic Stresses in Pear (Pyrus bretschneideri Rehd.) and in Comparison with Arabidopsis. (8th March 2017) - Tang, Jun; Lin, Jing; Li, Xiaogang; Yang, Qingsong; Cheng, Qunkang; Cheng, Zong-Ming (Max); Chang, Youhong
Abstract : A genome-wide identification and cloning of CaM genes in pear was conducted and in compared with Arabidopsis that indicated a conserved expansion of CaM genes in pear, and PbCaMs and AtCaMs had a similar distribution of cis-elements and expressions in response to salt and osmotic stress. In particular, PbCaM1 and PbCaM3 were both significantly upregulated in response to salt and osmotic stress in pear.